ASCARIASIS AS A CAUSE OF ACALCULUS EOSINOPHILIC CHOLECYSTITIS - A RARE CASE REPORT - RAMESH, KUNDAL; HARPAL, SINGH; CHAKMA, SWARUPA; KAUR, NAVPREET; DEEPIKA, DEEPIKA (International Journal of Clinical and Biomedical Research, 2016)
Acalculus eosinophilic cholecystitis is a variant of chronic cholecystitis which is an inflammation of gall bladder. Here we presents a case of female child of 10 years age with features of abdominal pain for 6 months which after investigations found to be of an eosinophilic cholecystitis cuased by Ascaris lumricoides- a rare entity.